Exploring Academic Culture: Unpacking its Definition and Structure (A Systematic Scoping Review) - Elena Tikhonova; Marina Kosycheva; Petr Kasatkin (National Research University Higher School of Economics, 2023)
Background: The concept of academic culture lacks a standardised definition, and its structural components have not been clearly outlined or universally agreed upon.  Purpose: This systematic scoping review aims to synthesise literature on academic culture, delineate its demographic characteristics, and extract definitions of academic culture and the components of its structure. Method: A search was conducted in the bibliographic database Scopus on August 2nd, 2023. Additionally, a search for related grey literature was carried out on August 3rd, 2023. We included studies published in English post-2018 that discuss academic culture. Titles and abstracts from the retrieved records were screened for relevance. Demographic characteristics related to academic culture were extracted from all search records. We then extracted statements from research articles, book chapters, editorials and reviews defining academic culture and  describing components of its structure. These identified structural components were categorised and thematically grouped, and then distributed according to the obtained components of academic culture. This review followed the guidelines of PRISMA-ScR to perform the study search and selection.   Results: The search yielded 961 records, of which 94 met our inclusion criteria. Predominantly consisting of journal articles, book chapters, or reviews (78.44%), only 23 of these records provided definitions of academic culture and its structure. Notably, different definitions frequently conflated academic and organisational culture. The structure of academic culture was delineated into three primary components and their subcomponents. This review also analysed the main focuses of academic culture during the specified period highlighting the importance of sustainable development across the three primary components of academic culture and shedding light on the diversity of academic culture models. Conclusion: This study successfully identified the key structural components and summarised the existing definitions of academic culture. It also highlighted principal research directions for studying academic culture. A significant aspect of this review is the investigation of various levels of academic culture, emphasising a meta-level of academic culture as a global, conventionally-determined dimension. This meta-level serves as a universal hallmark or the development of both national and local academic cultures.